2022
DOI: 10.1038/s41598-022-05697-8
|View full text |Cite
|
Sign up to set email alerts
|

Raster plots machine learning to predict the seizure liability of drugs and to identify drugs

Abstract: In vitro microelectrode array (MEA) assessment using human induced pluripotent stem cell (iPSC)-derived neurons holds promise as a method of seizure and toxicity evaluation. However, there are still issues surrounding the analysis methods used to predict seizure and toxicity liability as well as drug mechanisms of action. In the present study, we developed an artificial intelligence (AI) capable of predicting the seizure liability of drugs and identifying drugs using deep learning based on raster plots of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In many studies, ASD efficacy is inferred through changes in certain features relevant to ictogenesis, such as burst firing or measures of network activity propagation. A recent study demonstrated that a neural network could be trained on raster plots of spiking activity to distinguish between antiseizure and seizure‐provoking compounds 45 . Although the impact of different ASDs upon individual network features has been examined, 18,39 our study is unique by virtue of the wide range of features and the use of dimensionality reduction techniques, and because our primary aim is ASD classification rather than proof of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, ASD efficacy is inferred through changes in certain features relevant to ictogenesis, such as burst firing or measures of network activity propagation. A recent study demonstrated that a neural network could be trained on raster plots of spiking activity to distinguish between antiseizure and seizure‐provoking compounds 45 . Although the impact of different ASDs upon individual network features has been examined, 18,39 our study is unique by virtue of the wide range of features and the use of dimensionality reduction techniques, and because our primary aim is ASD classification rather than proof of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that a neural network could be trained on raster plots of spiking activity to distinguish between antiseizure and seizure-provoking compounds. 45 Although the impact of different ASDs upon individual network features has been examined, 18,39 our study is unique by virtue of the wide range of features and the use of dimensionality reduction techniques, and because our primary aim is ASD classification rather than proof of therapeutic efficacy. As such, we have not drawn conclusions in this work regarding the therapeutic application of drugs based on changes in network activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo analysis platforms with medium throughput have been used for the early detection of the seizure liability (ictogenicity) of novel drug candidates [ 4 ]. These platforms include brain slice and multi-electrode array analysis of drug-induced epileptiform activity in rodent cortical neurons or slices, or human induced pluripotent cells [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], and the analysis of motor behavior generated by zebrafish larvae exposed to convulsant drugs [ 15 , 16 ]. Despite the promising data and increasingly stronger predictive values achieved by applying machine-learning analysis approaches, the predictive accuracy remains limited or has not yet been vigorously validated in different laboratories [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a successful data acquisition in MEA assays might be costly and time-consuming. Finally, an in vitro to in vivo extrapolation (IVIVE) is required in MEA using hiPSC-derived neurons [28][29][30][31]. Traditional MEA measurements are preferred to analyze spikes with frequency components of 1 kHz or more and to investigate pathological mechanisms or drug efficacy [32].…”
Section: Introductionmentioning
confidence: 99%